Characteristics and management of sublingual allergen immunotherapy in children with allergic rhinitis and asthma induced by house dust mite allergens. Issue 1 (29th April 2014) - Trebuchon, Florence; Lhéritier‐Barrand, Michèle; David, Marie; Demoly, Pascal
Abstract: Background: Allergen immunotherapy is a recognised intervention in patients with allergies not responding to standard pharmacotherapy or in whom pharmacotherapy is contraindicated. We describe the sublingual immunotherapy (SLIT) regimens used in children and adolescents with house dust mite (HDM) respiratory allergies in France and assess the efficacy and safety of this treatment. Methods: This was a sub‐analysis of paediatric patients included in a previous retrospective, observational, multicentre study. Inclusion criteria were: age 5–17 years; respiratory allergy and proven sensitisation to HDM; at least 2 years follow‐up after SLIT initiation. The following data were recorded at SLIT initiation: clinical characteristics; sensitisation profile; concomitant symptomatic medications; details of SLIT protocol. During follow‐up and at the end of treatment the following data were recorded: any changes to SLIT treatment; any changes to symptomatic medications; symptom progression; adverse events. SLIT efficacy, patient compliance and satisfaction, and safety were assessed. Results: 736 paediatric patients were included in this analysis. Most patients (95.5%) had allergic rhinitis, which was moderate to severe persistent in 62.8%. Allergic asthma was present in 64.0% and was mild to moderate persistent in 52.7% of these patients. The majority of patients had rhinitis with asthma (59.5%). Three‐hundred and seventy five (62.3%) patients were polysensitised. Compliance was good in 86.5% of patients and SLIT was effective in 83.8%. Symptoms of rhinitis and asthma were improved in 64.6% and 64.3% of patients, respectively. A decrease in symptomatic medication was observed following SLIT initiation in patients with rhinitis and/or asthma. SLIT was well tolerated with mainly local reactions reported. Conclusions: HDM SLIT appears to be effective in children and adolescents with rhinitis and/or asthma due to HDM allergens, with no tolerability issues and similar benefits as in adults.